2017
DOI: 10.1016/j.ridd.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Early social communication in infants with fragile X syndrome and infant siblings of children with autism spectrum disorder

Abstract: Background Little research in fragile X syndrome (FXS) has prospectively examined early social communication. Aims To compare early social communication in infants with FXS, infant siblings of children with autism spectrum disorder (ASIBs), and typically developing (TD) infants. Methods and Procedures Participants were 18 infants with FXS, 21 ASIBs, and 22 TD infants between 7.5–14.5 months. Social communication was coded using the Communication Complexity Scale during the administration of Autism Observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
39
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 49 publications
8
39
0
2
Order By: Relevance
“…A strength of our study was the integration of cross-group comparisons to determine whether early trajectories of gesture use in FXS were similar to those of high-risk siblings. Very few studies have contrasted FXS with other high-risk populations (Cornish et al 2007), particularly in regard to gesture use and early development (Roberts et al 2016b;Caravella & Roberts 2017;Hahn et al 2017). We found that while both FXS and high-risk sibling populations are at increased risk for ASD, early gesture use was differentially associated with ASD symptom severity in these two groups.…”
Section: Impact Of Asd Symptom Severitymentioning
confidence: 57%
See 2 more Smart Citations
“…A strength of our study was the integration of cross-group comparisons to determine whether early trajectories of gesture use in FXS were similar to those of high-risk siblings. Very few studies have contrasted FXS with other high-risk populations (Cornish et al 2007), particularly in regard to gesture use and early development (Roberts et al 2016b;Caravella & Roberts 2017;Hahn et al 2017). We found that while both FXS and high-risk sibling populations are at increased risk for ASD, early gesture use was differentially associated with ASD symptom severity in these two groups.…”
Section: Impact Of Asd Symptom Severitymentioning
confidence: 57%
“…; Caravella & Roberts ; Hahn et al . ). We found that while both FXS and high‐risk sibling populations are at increased risk for ASD, early gesture use was differentially associated with ASD symptom severity in these two groups.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Hahn et al . ) or restricted use of gestures in general rather than focusing solely on IJA gestures (Flenthrope and Brady ). To our knowledge, there are no studies focusing specifically on IJA gaze shifts in infants with FXS and only one study analysing IJA gesture use in preschoolers with FXS.…”
Section: Initiating Joint Attention In Populations With Autism Spectrmentioning
confidence: 99%
“…Prior research on social communication in children with FXS has focused on language outcomes using visual attention (Kover et al 2015), preschool-aged children and adolescents rather than infants with FXS (Rogers et al 2003;Flenthrope and Brady 2010), other forms of JA (Marschik et al 2014;Hahn et al 2017) or restricted use of gestures in general rather than focusing solely on IJA gestures (Flenthrope and Brady 2010). To our knowledge, there are no studies focusing specifically on IJA gaze shifts in infants with FXS and only one study analysing IJA gesture use in preschoolers with FXS.…”
Section: Fragile X Syndromementioning
confidence: 99%